Implementasi Projek Penguatan Profil Pelajar Pancasila pada Dimensi Kebhinekaan Global di TK Amalia Kabupaten Bandung - 10030220001, Indah Alia Nurlatifah; Ayi Sobarna; Dinar Nur Inten (UNISBA Press, 2024)
Abstract. This research aims to (1) Find out the teacher's planning for the Project for Strengthening the Profile of Pancasila Students in the Global Diversity Dimension at Kindergarten Amalia, Bandung Regency, (2) Find out the implementation of the Project for Strengthening the Profile of Pancasila Students in the Dimension of Global Diversity at Kindergarten Amalia, Bandung Regency, (3) Find out evaluation in the implementation of the Project for Strengthening the Profile of Pancasila Students at Amalia Kindergarten, Bandung Regency, (4) Knowing the supporting factors and inhibiting factors in the implementation of the Project for Strengthening the Profile of Pancasila Students at Kindergarten Amalia, Bandung Regency. The method used is a qualitative descriptive approach. Data was collected through interviews and observations. The method used is Project Based Learning, students carry out exploration, assessment, interpretation and collection of information to produce various forms of learning outcomes. Evaluation of the Project for Strengthening Pancasila Student Profiles is carried out by opening a forum for teachers to identify problems that arise during or before the project, as well as child assessments carried out during the project. The main supporting factors at Kindergarten Amalia are the role of parents, school residents and the community. Abstrak. Penelitian ini bertujuan untuk (1) Mengetahui perencanaan guru pada Projek Penguatan Profil Pelajar Pancasila dalam dimensi Kebhinekaan Global di Tk Amalia Kabupaten Bandung, (2) Mengetahui pelaksanaan Projek Penguatan Profil Pelajar Pancasila dalam dimensi Kebhinekaan Global di Tk Amalia Kabupaten Bandung, (3) Mengetahui evaluasi dalam pelaksanaan Projek Penguatan Profil Pelajar Pancasila di Tk Amalia Kabupaten Bandung, (4) Mendengetahui Faktor pendukung dan Faktor Penghambat pada pelaksanaan Projek Penguatan Profil Pelajar Pancasila di Tk Amalia Kabupaten Bandung. Metode yang digunakan pendekatan deskriptif kualitatif. Data dikumpulkan melalui wawancara dan observasi. Metode yang digunakan adalah Pembelajaran Berbasis Proyek, peserta didik melakukan eksplorasi, penilaian, interpretasi, dan pengumpulan informasi untuk menghasilkan berbagai bentuk hasil belajar. Evaluasi Projek Penguatan Profil Pelajar Pancasila dilakukan dengan membuka forum bagi guru untuk mengidentifikasi masalah yang muncul selama atau sebelum proyek, serta penilaian anak dilakukan selama proyek berlangsung. Faktor pendukung utama di Tk Amalia adalah peran orangtua, warga sekolah, dan Masyarakat.